Thermally conductive member, metal base substrate, circuit board, electronic device, and method for manufacturing thermally conductive member

By employing a boron nitride powder with a pressure equivalent to the start of plastic deformation of 5.0 MPa or more, the variability in thermal conductivity of thermally conductive members is addressed, resulting in stable and improved thermal performance.

JP7647983B1Active Publication Date: 2025-03-18SUMITOMO BAKELITE CO LTD

Patent Information

Application Number
JP2024102758
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-03-18
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

There are variations in thermal conductivity in thermally conductive members containing boron nitride powder, which affects their performance.

Method used

Using a boron nitride powder with a pressure equivalent to the start of plastic deformation of 5.0 MPa or more, calculated by fitting using the Cooper-Eaton formula, to produce a thermally conductive member with improved thermal conductivity.

Benefits of technology

This approach allows for the stable production of thermally conductive members with enhanced thermal conductivity, reducing particle breakdown during manufacturing and maintaining high thermal conductivity in the final product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647983000001_ABST
    Figure 0007647983000001_ABST
Patent Text Reader

Abstract

Provided is a boron nitride powder that enables the stable production of thermally conductive members with improved thermal conductivity. [Solution] The boron nitride powder contains boron nitride particles, and has a plastic deformation initiation equivalent pressure of 5.0 MPa or more, calculated by fitting using the Cooper-Eaton equation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to boron nitride powder, a thermosetting resin composition, a thermally conductive member, a metal base substrate, a circuit board, an electronic device, and a method for producing a thermally conductive member. [Background technology]

[0002] Boron nitride powder has excellent thermal conductivity and is therefore used, for example, in thermally conductive members.

[0003] Patent Document 1 aims to provide a heat dissipation sheet with excellent thermal conductivity and electrical insulation, and a method for manufacturing the heat dissipation sheet with excellent thermal conductivity and electrical insulation. It discloses a heat dissipation sheet formed by molding a thermally conductive resin composition containing a resin and boron nitride powder that contains at least agglomerated boron nitride particles formed by agglomeration of hexagonal boron nitride primary particles, and the heat dissipation sheet has a partial discharge inception voltage of 2800 to 5000 kV / mm. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2022 / 149434 Summary of the Invention [Problem to be solved by the invention]

[0005] According to the investigations of the present inventors, it has become clear that there are cases where the thermal conductivity of a thermally conductive member containing boron nitride powder varies.

[0006] The present invention provides a boron nitride powder that can be used to stably produce thermally conductive members having improved thermal conductivity. [Means for solving the problem]

[0007] The inventors of the present invention have intensively studied to achieve the above problems. As a result, they have found that a thermally conductive sheet with improved thermal conductivity can be stably produced by using boron nitride powder having a plastic deformation initiation equivalent pressure of 5.0 MPa or more calculated by fitting according to the Cooper-Eaton formula, and thus completed the present invention.

[0008] [1] A boron nitride powder containing boron nitride particles, A boron nitride powder having a plastic deformation initiation equivalent pressure of 5.0 MPa or more calculated by fitting according to the Cooper-Eaton formula. [2] The boron nitride powder according to [1] above, having an orientation degree A after compression of 0.120 or more by the following (Method 1). (Method 1) For 0.85 ± 0.15 g of boron nitride powder filled in a cylindrical container with an inner diameter of 8.0 mm and a height of 40 mm, a load is applied at a pushing speed of 0.2 mm / s until the load reaches 500 N, and this operation is performed a total of 2 times to produce a compressed body of the boron nitride powder. In the X-ray diffraction spectrum of the compressed body obtained by the following <X-ray diffraction measurement method>, the diffraction peak intensity I of the 002 plane 002 and the diffraction peak intensity I of the 100 plane 100 are measured, The orientation degree A after compression is calculated from the following formula (1). Formula (1): Orientation degree A after compression = I 100 / I 002 <X-ray diffraction measurement method> Using CuKα rays as the radiation source, X-ray diffraction is performed by irradiating X-rays in the thickness direction of the compressed body under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scan speed of 4° / min. [3] The boron nitride powder according to [1] or [2] above, wherein the volume-based median diameter D of the boron nitride powder by the laser diffraction scattering method 50 is 0.1 μm or more and 100 μm or less. [4] The boron nitride powder according to any one of the above [1] to [3], which contains scaly boron nitride particles. [5] The boron nitride powder according to any one of the above [1] to [4], wherein the boron nitride particles include secondary particles constituted by scaly primary particles of boron nitride. [6] The boron nitride powder according to any one of the above [1] to [5], which can be used for a thermally conductive member. [7] The boron nitride powder according to any one of the above [1] to [7], which has a packing ratio of less than 0.74 after compression at 10 MPa. [8] A thermosetting resin composition comprising the boron nitride powder according to any one of [1] to [7] above and a thermosetting resin. [9] The thermosetting resin composition according to [8], wherein the content of the boron nitride powder is 50% by mass or more and 95% by mass or less, when the total amount of the thermosetting resin composition (excluding the solvent) is 100% by mass.

[10] The thermosetting resin composition according to [8] or [9], wherein the thermosetting resin comprises an epoxy resin.

[11] The thermosetting resin composition according to any one of [8] to

[10] above, wherein the content of the thermosetting resin is 5% by mass or more and 50% by mass or less, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100% by mass.

[12] The thermosetting resin composition according to any one of the above [8] to

[11] , further comprising a curing agent.

[13] The thermosetting resin composition according to

[12] , wherein the content of the curing agent is 0.01% by mass or more and 10% by mass or less, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100% by mass.

[14] Further comprising a solvent, The thermosetting resin composition according to any one of the above [8] to

[13] , which is in the form of a varnish as a whole.

[15] A thermally conductive member comprising a resin composition layer made of the thermosetting resin composition according to any one of [8] to

[14] above.

[16] The thermally conductive member according to

[15] above, wherein the entire member is in a sheet form.

[17] The thermally conductive member according to

[15] or

[16] , further comprising a substrate.

[18] The thermally conductive member according to any one of the above

[15] to

[17] , wherein the resin composition layer is in an uncured state, a B-stage state, or a C-stage state.

[19] The thermally conductive member according to any one of the above

[15] to

[18] , wherein the thermal conductivity in the thickness direction of the cured product of the resin composition layer, as measured by a laser flash method, is 10.0 W / (m K) or more.

[20] A metal substrate, an insulating layer, and a metal layer, in this order; A metal base board, wherein the insulating layer comprises a resin composition layer made of the thermosetting resin composition according to any one of [8] to

[14] above, or a cured product of the resin composition layer. [twenty one] A circuit board comprising the metal base substrate according to

[20] above, The metal layer comprises a circuit layer. [twenty two] The circuit board according to

[21] above; and an electronic component on the circuit board. [twenty three] A metal layer; an electronic component on a first surface of the metal layer; a thermally conductive member on a second surface of the metal layer opposite the first surface; a sealing resin layer that seals the electronic component and the metal layer, The thermally conductive member comprises a resin composition layer made of the thermosetting resin composition according to any one of [8] to

[14] above, or a cured product of the resin composition layer. [twenty four] A method for manufacturing a heat conductive member, comprising a step of selecting boron nitride powder having a plastic deformation initiation equivalent pressure of 5.0 MPa or more, calculated by fitting according to the Cooper-Eaton method.

[25] The method for manufacturing a heat conductive member according to any one of the above

[24] , further comprising a step of selecting boron nitride powder having an orientation degree A after compression of 0.120 or more by the following (Method 1). (Method 1) For 0.85 ± 0.15 g of boron nitride powder filled in a cylindrical container with an inner diameter of 8.0 mm and a height of 40 mm, a load is applied at a pushing speed of 0.2 mm / s until the load reaches 500 N, and this operation is performed a total of 2 times to produce a compressed body of boron nitride powder. In the X-ray diffraction spectrum of the compressed body obtained by the following <X-ray diffraction measurement method>, the diffraction peak intensity I of the 002 plane 002 and the diffraction peak intensity I of the 100 plane 100 are measured. The orientation degree A after compression is calculated from the following formula (1). Formula (1): Orientation degree A after compression = I 100 / I 002 <X-ray diffraction measurement method> Using CuKα rays as the radiation source, X-ray diffraction is performed by irradiating X-rays in the thickness direction of the compressed body under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scan speed of 4° / min.

[26] The method for manufacturing a heat conductive member according to the above

[24] or

[25] , further comprising a step of applying a resin composition layer made of a thermosetting resin composition containing the boron nitride powder and a thermosetting resin onto a substrate.

Advantages of the Invention

[0009] According to the present invention, it is possible to provide boron nitride powder capable of stably manufacturing a heat conductive member with improved heat conductivity.

Brief Description of the Drawings

[0010] [Figure 1]1 is a schematic cross-sectional view showing an example of the configuration of a metal base substrate according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing an example of a configuration of an electronic device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference symbols, and descriptions will be omitted as appropriate. The drawings are schematic views and do not correspond to actual dimensional ratios. Furthermore, "~" indicating a numerical range indicates "greater than or equal to" to "less than or equal to", unless otherwise specified.

[0012] [Boron nitride powder] The boron nitride powder of this embodiment (hereinafter also simply referred to as "powder") contains boron nitride. The boron nitride powder of this embodiment has a plastic deformation initiation equivalent pressure of 5.0 MPa or more, calculated by fitting to the Cooper-Eaton equation. The boron nitride powder of the present embodiment has the configuration as described above, and when the boron nitride powder is used, thermally conductive members with improved thermal conductivity can be stably manufactured.

[0013] The reason for this is not entirely clear, but the following reasons are presumed. Since the boron nitride powder of this embodiment has the aforementioned plastic deformation initiation equivalent pressure of 5.0 MPa or more, it is considered that the particles of the boron nitride powder are not easily broken even when a compressive pressure is applied. Therefore, it is considered that the thermal conductivity due to the thermal conduction through the particles of the boron nitride powder is not easily reduced even after the thermal conductive member manufacturing process by reducing the breakage of the particles of the boron nitride powder in the manufacturing process of the thermal conductive member. As a result, it is considered that when the boron nitride powder of this embodiment is used, it becomes possible to stably manufacture a thermal conductive member with improved thermal conductivity.

[0014] Next, each component of the boron nitride powder of this embodiment will be described with a specific example.

[0015] <Boron nitride powder> The boron nitride powder of the present embodiment contains boron nitride.

[0016] The boron nitride powder of the present embodiment preferably contains scaly boron nitride particles from the viewpoint of enabling more stable production of thermally conductive members with improved thermal conductivity.

[0017] From the viewpoint of more stably producing a thermally conductive member having improved thermal conductivity, the boron nitride particles of this embodiment more preferably contain secondary particles composed of scaly primary particles of boron nitride. The secondary particles are, for example, spherical particles. Here, the spherical shape is not limited to a perfect sphere, but includes an ellipsoid of revolution and a rounded shape formed by spheroidizing an aggregate of primary particles. In addition, the surface may be uneven as long as it is rounded overall. The secondary particles may be, for example, particles formed by sintering primary particles.

[0018] <Physical properties of boron nitride powder> The volume-based median diameter D of the boron nitride powder of this embodiment measured by a laser diffraction scattering method 50 From the viewpoint of enabling a more stable production of a thermally conductive member with improved thermal conductivity, the thickness is preferably 0.1 μm or more and 100 μm or less, more preferably 1 μm or more and 70 μm or less, even more preferably 5 μm or more and 50 μm or less, even more preferably 10 μm or more and 40 μm or less, and even more preferably 15 μm or more and 35 μm or less. The volume-based median diameter D 50 More specifically, the method described in the Examples can be used as the measurement method.

[0019] The pressure equivalent to the onset of plastic deformation of the boron nitride powder of this embodiment, calculated by fitting using the Cooper-Eaton equation, is 5.0 MPa or more, preferably 5.5 MPa or more, more preferably 6.0 MPa or more, even more preferably 6.3 MPa or more, even more preferably 6.5 MPa or more, even more preferably 7.0 MPa or more, even more preferably 7.5 MPa or more, even more preferably 8.0 MPa or more, and even more preferably 8.5 MPa or more, from the viewpoint of being able to stably produce thermally conductive components with improved thermal conductivity. The upper limit of the pressure equivalent to the initiation of plastic deformation is not particularly limited, but may be, for example, 15.0 MPa or less, optionally 14.0 MPa or less, optionally 13.0 MPa or less, optionally 12.0 MPa or less, optionally 11.0 MPa or less, optionally 10.0 MPa or less, or optionally 9.5 MPa or less. The pressure equivalent to the onset of plastic deformation of the boron nitride powder of this embodiment, calculated by fitting using the Cooper-Eaton equation, is, from the viewpoint of enabling stable production of thermally conductive components with improved thermal conductivity, preferably 5.0 MPa or more and 15.0 MPa or less, more preferably 5.5 MPa or more and 14.0 MPa or less, even more preferably 6.0 MPa or more and 13.0 MPa or less, even more preferably 6.3 MPa or more and 12.0 MPa or less, even more preferably 6.5 MPa or more and 11.0 MPa or less, even more preferably 7.0 MPa or more and 10.0 MPa or less, even more preferably 7.5 MPa or more and 10.0 MPa or less, even more preferably 8.0 MPa or more and 10.0 MPa or less, and even more preferably 8.5 MPa or more and 9.5 MPa or less. The pressure equivalent to the start of plastic deformation can be adjusted, for example, by adjusting the blending composition of small particles and coarse particles used in producing the boron nitride powder. Here, small particles are particles whose particle diameter is equal to or smaller than a predetermined value. Coarse particles are particles whose particle diameter is larger than a predetermined value. Small particles are, for example, particles having a median diameter D 50 When boron nitride powder having a median diameter of 20 μm or more and 40 μm or less is sieved through a sieve having an opening of 50 μm or more and 100 μm or less, particles that pass through the sieve can be used.50 When boron nitride powder with a particle size of 20 μm or more and 40 μm or less is sieved through a sieve having an aperture size of 50 μm or more and 100 μm or less, the particles remaining on the sieve can be used. In addition, as the method for measuring the equivalent pressure at the start of plastic deformation, specifically, the method described in the examples can be adopted.

[0020] From the viewpoint of more stably manufacturing a heat conductive member with improved thermal conductivity, the orientation degree A after compression of the boron nitride powder of the present embodiment by the following <Method 1> is preferably 0.120 or more, more preferably 0.125 or more, still more preferably 0.128 or more, still more preferably 0.130 or more, and still more preferably 0.132 or more. The upper limit of the orientation degree A after compression is not particularly limited. For example, it may be 0.200 or less, may be 0.180 or less, or may be 0.150 or less. From the viewpoint of more stably manufacturing a heat conductive member with improved thermal conductivity, the orientation degree A after compression is preferably 0.120 or more and 0.200 or less, more preferably 0.125 or more and 0.200 or less, still more preferably 0.128 or more and 0.200 or less, still more preferably 0.130 or more and 0.180 or less, and still more preferably 0.132 or more and 0.150 or less. The orientation degree A after compression can be adjusted, for example, by adjusting the blending composition of small-diameter particles and coarse particles used when producing the boron nitride powder. More specifically, as the method for measuring the orientation degree A after compression, the method described in the examples can be adopted.

[0021] <Method 1> A compressed body of boron nitride powder is produced by performing a total of two operations of applying a load to 0.85 ± 0.15 g of boron nitride powder filled in a cylindrical container with an inner diameter of 8.0 mm and a height of 40 mm until the load reaches 500 N at a pushing speed of 0.2 mm / s. In the X-ray diffraction spectrum of the compressed body obtained by the following <X-ray diffraction measurement method>, the diffraction peak intensity I of the 002 plane 002 and the diffraction peak intensity I of the 100 plane 100Measure and calculate the degree of orientation A after compression using the following formula (1). Formula (1): Degree of orientation A after compression = I 100 / I 002 <X-ray diffraction measurement method> Use CuKα rays as the radiation source. Perform X-ray diffraction by irradiating X-rays in the thickness direction of the compressed body under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scan speed of 4° / min.

[0022] From the viewpoint of being able to more stably manufacture a heat conductive member with improved thermal conductivity, the filling ratio (hereinafter also referred to as the filling ratio after compression) of the boron nitride powder of the present embodiment after compression at 10 MPa is preferably less than 0.74, more preferably 0.50 or more and 0.70 or less, still more preferably 0.53 or more and 0.68 or less, still more preferably 0.55 or more and 0.65 or less, and still more preferably 0.57 or more and 0.63 or less. The filling ratio after compression can be adjusted, for example, by adjusting the blending composition of small-diameter particles and coarse particles used when producing the boron nitride powder. More specifically, the measurement method of the filling ratio after compression can adopt the method described in the examples.

[0023] <Uses of boron nitride powder> Next, the uses of the boron nitride powder of the present embodiment will be described.

[0024] Since the boron nitride powder of the present embodiment can more stably manufacture a heat conductive member with improved thermal conductivity, it can be used for heat conductive members. Further, the heat conductive member may contain, for example, a metal member or the like. The shape of the heat conductive member is not particularly limited and can be any shape.

[0025] [Thermosetting resin composition] The thermosetting resin composition of the present embodiment contains the boron nitride powder of the present embodiment and a thermosetting resin (A). The thermosetting resin composition of the present embodiment may contain components other than the boron nitride powder of the present embodiment and the thermosetting resin (A).

[0026] From the viewpoint of enabling a more stable production of a thermally conductive member with improved thermal conductivity, the content of boron nitride powder in the thermosetting resin composition of this embodiment is preferably 50 mass% or more and 95 mass% or less, more preferably 55 mass% or more and 90 mass% or less, even more preferably 60 mass% or more and 85 mass% or less, even more preferably 65 mass% or more and 82 mass% or less, and even more preferably 70 mass% or more and 80 mass% or less, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100 mass%.

[0027] <Thermosetting resin (A)> Examples of the thermosetting resin (A) of the present embodiment include epoxy resins, cyanate resins, polyimide resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, silicone resins, bismaleimide resins, acrylic resins, etc. The thermosetting resin (A) preferably contains an epoxy resin.

[0028] Examples of the epoxy resin (A1) of this embodiment include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol S type epoxy resin, bisphenol M type epoxy resin (4,4'-(1,3-phenylenediisopridiene) bisphenol type epoxy resin), bisphenol P type epoxy resin (4,4'-(1,4-phenylenediisopridiene) bisphenol type epoxy resin), and bisphenol Z type epoxy resin (4,4'-cyclohexydiene bisphenol type epoxy resin); phenol novolac type epoxy resin, cresol novolac type epoxy resin, trisphenol group methane type novolac type epoxy resin, tetraphenol novolac type epoxy resin, and the like. aryl alkylene type epoxy resins such as xylylene type epoxy resins and biphenyl aralkyl type epoxy resins; naphthalene type epoxy resins such as naphthylene ether type epoxy resins, naphthol type epoxy resins, naphthalene diol type epoxy resins, difunctional to tetrafunctional epoxy type naphthalene resins, binaphthyl type epoxy resins and naphthalene aralkyl type epoxy resins; anthracene type epoxy resins; phenoxy type epoxy resins; dicyclopentadiene type epoxy resins; norbornene type epoxy resins; adamantane type epoxy resins; and fluorene type epoxy resins.

[0029] The epoxy resin (A1) of the present embodiment preferably contains one or more resins selected from the group consisting of bisphenol-type epoxy resins, novolac-type epoxy resins, biphenyl-type epoxy resins, aryl alkylene-type epoxy resins, naphthalene-type epoxy resins, anthracene-type epoxy resins, and dicyclopentadiene-type epoxy resins, and more preferably contains one or more resins selected from the group consisting of bisphenol-type epoxy resins and dicyclopentadiene-type epoxy resins.

[0030] From the viewpoint of enabling a more stable production of a thermally conductive member with improved thermal conductivity, the content of the thermosetting resin (A) in the thermosetting resin composition of this embodiment is, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100 mass%, preferably 5 mass% or more and 50 mass% or less, more preferably 7 mass% or more and 45 mass% or less, even more preferably 9 mass% or more and 40 mass% or less, even more preferably 11 mass% or more and 35 mass% or less, even more preferably 13 mass% or more and 30 mass% or less, and even more preferably 15 mass% or more and 25 mass% or less.

[0031] <Hardening agent (B)> The thermosetting resin composition of the present embodiment preferably contains one or more selected from the group consisting of a curing agent (B) and a curing catalyst (C), and more preferably contains a curing agent (B). Examples of the curing agent (B) of the present embodiment include amine compounds such as aliphatic polyamines, aromatic polyamines, aromatic diamines, and diamine diamide, acid anhydrides such as alicyclic acid anhydrides and aromatic acid anhydrides, phenol compounds such as novolac-type phenolic resins (phenol-based curing agents (B1)), and imidazole compounds. The thermosetting resin composition of the present embodiment further preferably contains one or more selected from the group consisting of a phenol-based curing agent (B1) and a curing catalyst (C), and further preferably contains both a phenol-based curing agent (B1) and a curing catalyst (C).

[0032] <Phenol-based hardener (B1)> Examples of the phenol-based curing agent (B1) of the present embodiment include novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, trisphenolmethane-type novolac resin, naphthol novolac resin, and aminotriazine novolac resin; modified phenolic resins such as terpene-modified phenolic resin and dicyclopentadiene-modified phenolic resin; aralkyl-type resins such as phenol aralkyl resins having a phenylene skeleton and / or a biphenylene skeleton and naphthol aralkyl resins having a phenylene skeleton and / or a biphenylene skeleton; bisphenol compounds such as bisphenol A and bisphenol F; and resol-type phenolic resins. The phenol-based curing agent (B1) of the present embodiment preferably contains one or more phenol resins selected from the group consisting of novolac-type phenol resins and resol-type phenol resins, and more preferably contains a novolac-type phenol resin.

[0033] The content of the curing agent (B) in the thermosetting resin composition of the present embodiment, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100 mass%, is preferably 0.01 mass% or more and 10 mass% or less, more preferably 0.1 mass% or more and 9 mass% or less, even more preferably 1 mass% or more and 8 mass% or less, even more preferably 2 mass% or more and 7 mass% or less, even more preferably 3 mass% or more and 6 mass% or less, and even more preferably 4 mass% or more and 6 mass% or less.

[0034] <Curing catalyst (C)> Examples of the curing catalyst (C) of the present embodiment include organic metal salts such as zinc naphthenate, cobalt naphthenate, tin octylate, cobalt octylate, bisacetylacetonate cobalt (II), and trisacetylacetonate cobalt (III); tertiary amines such as triethylamine, tributylamine, and 1,4-diazabicyclo[2.2.2]octane; 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 2,4-diethylimidazole, and 2-phenyl-4-methyl-5-hydroxyimidazole. imidazoles such as midazole and 2-phenyl-4,5-dihydroxymethylimidazole; organic phosphorus compounds such as triphenylphosphine, tri-p-tolylphosphine, tetraphenylphosphonium tetraphenylborate, triphenylphosphine triphenylborane, and 1,2-bis-(diphenylphosphino)ethane; phenolic compounds such as phenol, bisphenol A, and nonylphenol; organic acids such as acetic acid, benzoic acid, salicylic acid, and p-toluenesulfonic acid; and the like, or mixtures thereof.

[0035] From the viewpoint of improving the glass transition temperature and reducing the linear expansion coefficient, the content of the curing catalyst (C) in the thermosetting resin composition of the present embodiment is preferably 0.001 mass % or more and 1 mass % or less, more preferably 0.005 mass % or more and 0.8 mass % or less, even more preferably 0.01 mass % or more and 0.5 mass % or less, even more preferably 0.05 mass % or more and 0.4 mass % or less, and even more preferably 0.1 mass % or more and 0.3 mass % or less, when the total amount of the thermosetting resin composition (excluding the solvent) is taken as 100 mass %.

[0036] <Other ingredients> The thermosetting resin composition of this embodiment may contain components other than the boron nitride powder of this embodiment, the thermosetting resin (A), the curing agent (B), and the curing catalyst (C). Examples of the other components include fillers, coupling agents, phenoxy resins, antioxidants, leveling agents, defoamers, and dispersants. Examples of the fillers include silica, alumina, aluminum nitride, and silicon carbide. Examples of the coupling agents include epoxy silane coupling agents, cationic silane coupling agents, amino silane coupling agents, titanate coupling agents, and silicone oil coupling agents. Examples of the phenoxy resin (E) include phenoxy resins having a bisphenol skeleton, phenoxy resins having a naphthalene skeleton, phenoxy resins having an anthracene skeleton, and phenoxy resins having a biphenyl skeleton.

[0037] <Solvent> The thermosetting resin composition of the present embodiment may further contain a solvent. In this case, the entire thermosetting resin composition is in a varnish state. Examples of the solvent include methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, and cyclohexanone.

[0038] The content of the solvent in the thermosetting resin composition of this embodiment is, for example, 40 parts by mass or more and 85 parts by mass or less, when the total of the content of the boron nitride powder and the content of the thermosetting resin (A) in the thermosetting resin composition is 100 parts by mass.

[0039] <Method for producing thermosetting resin composition> The method for producing the thermosetting resin composition of the present embodiment is not particularly limited, and a known method can be used. For example, more specifically, the method described in the examples can be used as the method for producing the thermosetting resin composition of the present embodiment.

[0040] [Resin sheet] The resin sheet of the present embodiment includes a resin composition layer made of the thermosetting resin composition of the present embodiment. The resin composition layer is preferably in a B-stage state. The resin sheet has a form, for example, of a substrate and a resin composition layer made of the thermosetting resin composition of the present embodiment provided on the substrate.

[0041] The resin sheet of the present embodiment can be obtained, for example, by applying a varnish-like thermosetting resin composition onto a substrate to obtain a coating film, and then performing a solvent removal treatment. The solvent content in the resin sheet is preferably 10 mass% or less based on the entire thermosetting resin composition. For example, the solvent removal treatment can be performed under conditions of 80°C to 200°C and 1 minute to 30 minutes.

[0042] The planar shape of the resin sheet of this embodiment is not particularly limited and can be appropriately selected in accordance with the shapes of the heat sink, heat generator, etc., but can be, for example, rectangular. The resin composition layer of the resin sheet of the present embodiment has a thickness of, for example, 50 μm or more and 500 μm or less from the viewpoint of further improving the balance of mechanical strength, heat resistance, insulating properties, and heat dissipation properties.

[0043] The substrate includes, for example, one or more selected from the group consisting of resin films and metal foils. Examples of the resin film include polyolefin films such as polyethylene films and polypropylene films; polyester films such as polyethylene terephthalate films and polybutylene terephthalate films; polycarbonate films; fluorine-based resin films; and polyimide resin films. Examples of the metal foil include copper foil, copper-based alloy foil, aluminum foil, aluminum-based alloy foil, iron foil, iron-based alloy foil, silver foil, silver-based alloy foil, gold foil, gold-based alloy foil, zinc foil, zinc-based alloy foil, nickel foil, nickel-based alloy foil, tin foil, and tin-based alloy foil. The thickness of the substrate is, for example, 10 μm or more and 500 μm or less.

[0044] The resin sheet of the present embodiment can be used for various substrate applications. From the viewpoint of the balance between thermal conductivity and heat resistance, the resin sheet can be preferably used as a material for a power module substrate.

[0045] [Thermal conductive material] The thermally conductive member of the present embodiment includes a resin composition layer made of the thermosetting resin composition of the present embodiment.

[0046] The thermally conductive member of the present embodiment is preferably entirely in a sheet shape from the viewpoint of improving ease of handling. The thermally conductive member is, for example, a thermally conductive sheet.

[0047] The thermally conductive member of the present embodiment further includes a base material. Such a thermally conductive member is, for example, the resin sheet of the present embodiment before the base material is peeled off.

[0048] The resin composition layer contained in the thermally conductive member of the present embodiment may be in an uncured state, a B-stage state, or a C-stage state. The resin composition layer is preferably in a B-stage state or a C-stage state.

[0049] In the thermally conductive member of this embodiment, the thermal conductivity in the thickness direction of the cured product of the resin composition layer (i.e., the resin composition layer in a C-stage state), as measured by a laser flash method, is, from the viewpoint of further improving thermal conductivity, preferably 10.0 W / (m·K) or more, more preferably 10.5 W / (m·K) or more, even more preferably 11.0 W / (m·K) or more, even more preferably 11.5 W / (m·K) or more, even more preferably 12.0 W / (m·K) or more, even more preferably 12.5 W / (m·K) or more, and even more preferably 13.0 W / (m·K) or more.

[0050] The upper limit of the thermal conductivity in the thickness direction of the cured resin composition layer is not particularly limited, but is, for example, 20.0 W / (m·K) or less, optionally 18.0 W / (m·K) or less, or optionally 15.0 W / (m·K) or less.

[0051] From the viewpoint of further improving thermal conductivity, the thermal conductivity in the thickness direction of the layer of the cured product of the resin composition layer is preferably 10.0 W / (m·K) or more and 20.0 W / (m·K) or less, more preferably 10.5 W / (m·K) or more and 20.0 W / (m·K) or less, even more preferably 11.0 W / (m·K) or more and 20.0 W / (m·K) or less, even more preferably 11.5 W / (m·K) or more and 20.0 W / (m·K) or less, even more preferably 12.0 W / (m·K) or more and 18.0 W / (m·K) or less, even more preferably 12.5 W / (m·K) or more and 15.0 W / (m·K) or less, and even more preferably 13.0 W / (m·K) or more and 15.0 W / (m·K) or less. More specifically, the method for measuring the thermal conductivity can be the method described in the Examples.

[0052] The thermally conductive member of the present embodiment is used, for example, as a thermally conductive material interposed between a heat generating body and a heat dissipating body. Examples of the heat generating body include a semiconductor element, an LED element, a substrate on which a semiconductor element or an LED element is mounted, a Central Processing Unit (CPU), a power semiconductor, a lithium ion battery, and a fuel cell. Examples of the heat dissipating body include a heat sink, a heat spreader, and a heat dissipating (cooling) fin.

[0053] Furthermore, the thermally conductive member of the present embodiment can be provided, for example, at a bonding interface in an electronic device where high thermal conductivity is required, and can promote thermal conduction from a heat generating body to a heat sink, thereby suppressing failures caused by characteristic fluctuations in semiconductor chips, etc., and improving the stability of the electronic device.

[0054] The thermally conductive member of the present embodiment can be used for various substrate applications, and from the viewpoint of the balance between thermal conductivity and heat resistance, can be preferably used as a material for a power module substrate.

[0055] <Method of manufacturing thermally conductive member> Hereinafter, each step of the method for producing the thermally conductive member of this embodiment will be described. The thermosetting resin composition used in the method for producing a thermally conductive member of the present embodiment preferably contains the thermosetting resin composition of the present embodiment.

[0056] The method for producing the thermally conductive member of this embodiment includes the following steps. Step 1: Select boron nitride powder with a plastic deformation onset equivalent pressure of 5.0 MPa or more, calculated by fitting with the Cooper-Eaton equation. The method for producing a thermally conductive member of this embodiment has the above-described configuration, and therefore can stably produce a thermally conductive member with improved thermal conductivity.

[0057] <Process 1> In step 1, boron nitride powder is selected based on the pressure equivalent to the onset of plastic deformation calculated by fitting using the Cooper-Eaton equation. From the viewpoint of stably producing a thermally conductive member with improved thermal conductivity, the pressure equivalent to the onset of plastic deformation of the boron nitride powder is 5.0 MPa or more, preferably 5.0 MPa or more and 15.0 MPa or less, more preferably 5.5 MPa or more and 14.0 MPa or less, even more preferably 6.0 MPa or more and 13.0 MPa or less, even more preferably 6.3 MPa or more and 12.0 MPa or less, even more preferably 6.5 MPa or more and 11.0 MPa or less, even more preferably 7.0 MPa or more and 10.0 MPa or less, even more preferably 7.5 MPa or more and 10.0 MPa or less, even more preferably 8.0 MPa or more and 10.0 MPa or less, even more preferably 8.5 MPa or more and 9.5 MPa or less. Specifically, the method for measuring the pressure equivalent to the start of plastic deformation can be the method described in the Examples.

[0058] The method for producing the thermally conductive member of this embodiment may further include the following step 2. Step 2: Select boron nitride powder having a degree of orientation A of 0.120 or more after compression, obtained by the above-mentioned <Method 1>.

[0059] <Process 2> In step 2, boron nitride powder is selected based on the degree of orientation A after compression by the above-mentioned <Method 1>. From the viewpoint of enabling more stable production of thermally conductive members with improved thermal conductivity, the degree of orientation A after compression of the boron nitride powder is preferably 0.120 or more and 0.200 or less, more preferably 0.125 or more and 0.200 or less, even more preferably 0.128 or more and 0.200 or less, even more preferably 0.130 or more and 0.180 or less, and even more preferably 0.132 or more and 0.150 or less.

[0060] The method for producing the thermally conductive member of this embodiment may further include the following step 3. Step 3: A resin composition layer made of a thermosetting resin composition containing boron nitride powder and a thermosetting resin is applied onto the substrate. The method for producing a thermally conductive member of this embodiment has the above-mentioned configuration, and therefore can more stably produce a thermally conductive member having improved thermal conductivity. Step 3 can be carried out, for example, by applying a varnish-like thermosetting resin composition onto a substrate and then subjecting the resulting coating film to a solvent removal treatment.

[0061] [Metal base board] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a metal base substrate 100 of this embodiment. The metal base substrate 100 of this embodiment includes, in this order, a metal substrate 101, an insulating layer 102, and a metal layer 103. The insulating layer 102 includes a resin composition layer made of the thermosetting resin composition of this embodiment, or a cured product of the resin composition layer.

[0062] The thickness of the insulating layer 102 is preferably 10 μm or more and 400 μm or less, more preferably 30 μm or more and 350 μm or less, even more preferably 50 μm or more and 300 μm or less, and even more preferably 100 μm or more and 250 μm or less, from the viewpoint of improving the mechanical strength, heat resistance, and insulating properties, as well as improving the heat dissipation properties of the entire metal base substrate 100.

[0063] The metal layer 103 is a layer used for circuit processing, which is provided on the insulating layer 102. Examples of metals that form the metal layer 103 include copper, copper alloys, aluminum, aluminum alloys, nickel, iron, and tin.

[0064] The thickness of metal layer 103 is preferably 0.01 mm or more and 10.0 mm or less, more preferably 0.025 mm or more and 5.0 mm or less, even more preferably 0.05 mm or more and 3.0 mm or less, even more preferably 0.10 mm or more and 2.0 mm or less, and even more preferably 0.25 mm or more and 1.0 mm or less, from the viewpoint of reducing heat generation in the circuit pattern even in applications requiring high current, improving circuit processability, and making the entire substrate thinner.

[0065] The metal substrate 101 has a role of dissipating heat accumulated in the metal base substrate 100. There are no particular limitations on the metal substrate 101 as long as it is a heat-dissipating metal substrate.

[0066] The thickness of metal substrate 101 is preferably 0.01 mm or more and 20.0 mm or less, more preferably 0.1 mm or more and 15.0 mm or less, even more preferably 1.0 mm or more and 7.5 mm or less, and even more preferably 2.0 mm or more and 5.0 mm or less, from the viewpoints of improving processability in external processing, cutting processing, etc., making the entire substrate thinner, and improving heat dissipation properties.

[0067] The metal base substrate 100 can have a metal layer 103 that is circuitized by etching or the like into a circuit pattern. In the metal base substrate 100, a solder resist layer (not shown) may be formed on the outermost layer, thereby exposing connection electrodes so that electronic components can be mounted by exposure and development.

[0068] [Circuit board] The circuit board of this embodiment includes the metal base substrate 100 of this embodiment. In the circuit board of this embodiment, the metal layer 103 includes a circuit layer. The circuit layer can be obtained by processing the metal layer 103 of the metal base substrate 100 into a circuit pattern by etching or the like.

[0069] The circuit board of the present embodiment can be used for various substrate applications, and from the viewpoint of the balance between thermal conductivity and heat resistance, can be preferably used as a power module substrate.

[0070] [Electronic equipment] The metal base substrate 100 and the circuit board of this embodiment can be used in various applications requiring heat dissipation and insulation properties, for example, in electronic devices such as semiconductor devices. FIG. 2 is a schematic cross-sectional view showing an example of the configuration of an electronic device 200 according to this embodiment. An electronic device 200 of this embodiment includes the circuit board of this embodiment and an electronic component 201 on the circuit board. The metal base substrate 100 (circuit board) on which a circuit is processed can function as a heat spreader against heat from the electronic components 201 (various heat generating elements) that generate heat during operation.

[0071] Electronic device 200 of the present embodiment includes metal layer 103, electronic component 201 on a first surface of metal layer 103, a thermally conductive member on a second surface opposite to the first surface, and a sealing resin layer 205 that seals electronic component 201 and metal layer 103. In electronic device 200 of the present embodiment, the thermally conductive member includes a resin composition layer made of the thermosetting resin composition of the present embodiment, or a cured product of the resin composition layer. In the electronic device 200 of this embodiment, the thermally conductive member may be, for example, the insulating layer 102 included in the metal base substrate 100 . The first surface of the metal layer 103 of the metal base substrate 100 of this embodiment is the upper surface of the metal layer 103 in Fig. 2. The second surface of the metal layer 103 of the metal base substrate 100 of this embodiment is the lower surface of the metal layer 103 in Fig. 2.

[0072] 2 has an electronic component 201 such as a semiconductor element mounted on a metal layer 103 of a metal base substrate 100 via an adhesive layer 202 such as a die attach material. The electronic component 201 is connected to a connection electrode portion formed on the metal base substrate 100 via a bonding wire 203, and is mounted on the metal base substrate 100. The electronic component 201 is then collectively sealed on the metal base substrate 100 by a sealing resin layer 205.

[0073] A heat sink 207 is provided on the metal substrate 101 side of the metal base substrate 100 via a thermally conductive layer 209 (thermal interface material (TIM)). From the viewpoint of thermal conductivity, examples of materials for the heat sink 207 include metals such as aluminum, iron, and copper.

[0074] The electronic component is preferably, but not limited to, a semiconductor element. Examples of semiconductor elements include, but are not limited to, integrated circuits, large scale integrated circuits, transistors, thyristors, diodes, solid-state imaging elements, LEDs, and power semiconductor elements. Examples of power semiconductor elements include rectifier diodes, power transistors, power MOSFETs, insulated gate bipolar transistors (IGBTs), thyristors, gate turn-off thyristors (GTOs), and triacs.

[0075] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Furthermore, the present invention is not limited to the above-described embodiment, and modifications and improvements that do not impair the effects of the present invention are included in the present invention. EXAMPLES

[0076] Hereinafter, the present embodiment will be described in detail with reference to examples, etc. However, the present embodiment is not limited to the description of these examples.

[0077] First, the materials used to prepare the boron nitride powder in each example are shown.

[0078] Large particles It was prepared according to the <Preparation of coarse particles> below. Small particles It was prepared according to the <Preparation of small particles> below.

[0079] <Preparation of coarse particles> Boron nitride 1 (product name: HP-40MF100, manufactured by JFE Mineral Co., Ltd., median diameter D 50 Boron nitride 1 was passed through a sieve with an opening of 75 μm. The particles remaining on the sieve were collected to obtain coarse particles.

[0080] <Preparation of small particles> Boron nitride 1 (product name: HP-40MF100, manufactured by JFE Mineral Co., Ltd., median diameter D 50 Boron nitride 1 was passed through a sieve with an opening size of 75 μm. The particles that passed through the sieve were collected to obtain small diameter particles.

[0081] [Examples 1 to 5, Comparative Examples 1 to 2] <Preparation of boron nitride powder> The coarse particles and the small particles were mixed according to the composition shown in Table 1 to obtain boron nitride powder for each example. Next, the physical properties of the boron nitride powder of each example and the physical properties of the thermosetting resin composition containing the boron nitride powder of each example were measured by the following methods. The results are shown in Table 1.

[0082] <Volume-based median diameter D measured by laser diffraction scattering method 50 > Using a laser diffraction particle size distribution analyzer (product name: LA-950V2, manufactured by Horiba, Ltd.), the volume-based median diameter D of each boron nitride powder was measured by the laser diffraction scattering method. 50 Here, the median diameter D of the boron nitride powder was measured. 50 was calculated in the following steps: 0.1 g of boron nitride powder and 1.5 mL of water were placed in a 2 mL cylindrical container. Next, detergent (product name: Mama Lemon, manufactured by Lion Corporation) was mixed with pure water at a detergent:pure water ratio of 1:100 (volume ratio) to prepare a dispersant. Next, three drops of the dispersant were dropped into the cylindrical container with a dropper, and the container was shaken to prepare a sample. The prepared sample was added to pure water (with ultrasonic waves and stirring) circulating in the measurement device, and the particle size distribution of the boron nitride powder was measured. From the particle size distribution of the boron nitride powder, the median diameter D 50 was calculated.

[0083] <Pressure equivalent to the start of plastic deformation> For each boron nitride powder, the equivalent pressure at which plastic deformation begins was calculated by fitting with the Cooper-Eaton equation according to the <Method for calculating equivalent pressure at which plastic deformation begins> below. The calculation of the equivalent pressure at which plastic deformation begins was performed twice in total, and the average of the two calculations was taken as the equivalent pressure at which plastic deformation begins for each boron nitride powder.

[0084] <How to calculate the pressure equivalent to the start of plastic deformation> First, the Cooper-Eaton equation is expressed by the following equation (3). Equation (3): [{V(0)−V(P)} / {V(0)−V(∞)}]=A1exp(-k1 / P)+(1−A1)exp(-k2 / P) In the above equation (3), pressure P represents the pressure applied to the boron nitride powder. Apparent volume V(0) represents the apparent volume of boron nitride powder before compression. Apparent volume V(P) represents the apparent volume of boron nitride powder when compressed at pressure P [MPa]. Apparent volume V(∞) represents the apparent volume of boron nitride powder when it is assumed that there are no voids in the boron nitride powder. Coefficient A1 represents a constant between 0 and 1. Coefficient k1 represents a constant greater than or equal to 0. Coefficient k2 represents a constant greater than or equal to 0, and is also called the pressure equivalent to the start of plastic deformation.

[0085] For the above formula (3), the value of {V(0)-V(P)} / {V(0)-V(∞)} was calculated for each of P = 0, 0.6, 1.2, 1.8, 3.0, 8.0, and 10.0 [MPa]. The value of {V(0)-V(P)} / {V(0)-V(∞)} was then plotted against the value of pressure P [MPa]. The coefficients A1, k1, and k2 were calculated from the plotted results using the least squares method. The result for coefficient k2 (equivalent pressure at which plastic deformation begins) is shown in Table 1. A method for calculating each apparent volume will be specifically described below.

[0086] Calculation of apparent volume V(0) First, the apparent volume V(0) of each boron nitride powder was calculated according to the following method.

[0087] 0.85g±0.15g of each boron nitride powder was weighed out and placed in a cylindrical container (inner diameter 8.0mm x height 40mm) attached to a powder bed shear force measuring device (product name: NS-S500, manufactured by Nanoseeds Co., Ltd.). At this time, the thickness of the boron nitride powder was made uniform within the cylindrical container. In the following, the radius of the inner diameter of the cylindrical container may be referred to as the radius r.

[0088] Next, the thickness T(0) of the boron nitride powder before compression was measured using a laser displacement meter attached to the powder bed shear force measuring device. The thickness T(0) was the value of the part with the smallest thickness in the boron nitride powder before compression. The apparent volume V(0) was calculated from the following formula (4). Equation (4): Apparent volume V(0) = (pi) × (radius r) 2 ×T(0)

[0089] Calculation of apparent volume V(P) Next, the apparent volume V(P) of each boron nitride powder was calculated according to the following method: Specifically, the apparent volumes V(P) were calculated as V(0.6), V(1.2), V(1.8), V(3.0), V(8.0), and V(10.0), respectively.

[0090] 0.85 g±0.15 g of the boron nitride powder of each example was weighed out and placed in the cylindrical container, so that the thickness of the boron nitride powder was uniform within the cylindrical container.

[0091] Next, the boron nitride powder of each example was subjected to the following (V(P) measurement operation). At this time, the specified load was changed for each pressure P applied to the boron nitride powder, and the following (V(P) measurement operation) was performed. The specified load for each pressure P was set to 30N at 0.6MPa, 60N at 1.2MPa, 90N at 1.8MPa, 150N at 3.0MPa, 400N at 8.0MPa, and 500N at 10.0MPa.

[0092] (V(P) measurement operation) With the boron nitride powder placed in the cylindrical container, a load was applied to the entire upper surface of the boron nitride powder at a pressing speed of 0.2 mm / s until the load on the boron nitride powder reached a predetermined load. After that, the thickness T(P) of the boron nitride powder compressed under the predetermined load (pressure P) was measured using the laser displacement meter. The thickness T(P) was the value of the minimum thickness of the boron nitride powder compressed under the predetermined load (pressure P). The apparent volume V(P) was calculated from the following formula (5). Equation (5): Apparent volume V(P) = (pi) × (radius r) 2 ×T(P)

[0093] Calculation of apparent volume V(∞) Next, the apparent volume V(∞) of the boron nitride powder of each example was calculated from the following formula (6). Equation (6) Apparent volume V(∞) = (mass of boron nitride powder in cylindrical container) / (true density of boron nitride powder)

[0094] <Filling rate after compression at 10MPa> The packing ratio of each boron nitride powder after compression at 10 MPa (hereinafter also referred to as the packing ratio after compression) was calculated from the following formula (8). The results are shown in Table 1. Equation (8): Filling rate after compression = V(∞) / V(10.0)

[0095] <X-ray Diffraction Measurement Method> CuKα rays were used as the radiation source. X-rays were irradiated onto the boron nitride powder under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scan speed of 4° / min to perform X-ray diffraction. The details of the measurement were as follows.

[0096] X-ray diffractometer: Ultima IV (manufactured by Rigaku) Radiation source: CuKα rays Measurement optical system: Convergent method Scanning axis: 2θ / θ Sampling width: 0.02° Scan speed: 4° / min Divergence slit: 2 / 3° Divergence vertical limiting slit: 10 mm Scattering slit: 1.17 mm Receiving slit: 0.3 mm Offset angle 0° Voltage: 40 kV Current: 40 mA

[0097] <Orientation Degree after Compression> A cylindrical container with an inner diameter of 8.0 mm and a height of 40 mm was filled with 0.85 ± 0.15 g of boron nitride powder. A compression body of the boron nitride powder was prepared by performing a total of two operations of applying a load to the entire upper surface of the filled boron nitride powder until the load reached 500 N at a pushing speed of 0.2 mm / s. In the X-ray diffraction spectrum of the compression body obtained by the above <X-ray Diffraction Measurement Method>, the diffraction peak intensity I of the 002 plane 002 and the diffraction peak intensity I of the 100 plane 100 were measured. The orientation degree A after compression was calculated from the following formula (1). Formula (1): Orientation degree A after compression = I 100 / I 002 The calculation of the orientation degree A after compression was performed a total of three times. The average value of the three times was taken as the orientation degree A after compression of the boron nitride powder in each example.

[0098] <Evaluation of Thermal Conductivity> Using the boron nitride powder of each example, a thermosetting resin composition was prepared according to the following <Preparation of thermosetting resin composition>. Then, using the prepared cured product, the thermal conductivity was measured according to the following <Method of measuring thermal conductivity>. After the measurement, the thermal conductivity of the cured product of the thermosetting resin composition of each example was evaluated.

[0099] <Preparation of Thermosetting Resin Composition> In addition to the boron nitride powder in each example, the thermosetting resin composition used the following <Materials for thermosetting resin composition>. The composition of the thermosetting resin composition was as shown in the following <Composition of thermosetting resin composition>.

[0100] <Materials for thermosetting resin composition> Thermosetting resin (A) (epoxy resin (A1)) Epoxy resin 1: Epoxy resin having a dicyclopentadiene skeleton (XD-1000, manufactured by Nippon Kayaku Co., Ltd.) Epoxy resin 2: Bisphenol A type epoxy resin (828, manufactured by Mitsubishi Chemical Corporation) Hardener (B) (phenol-based hardener (B1)): Trisphenylmethane-type phenol novolac resin (MEH-7500, manufactured by Meiwa Kasei Co., Ltd.) Curing catalyst (C): 2-phenyl-4,5-dihydroxymethylimidazole (2PHZ-PW, manufactured by Shikoku Kasei Co., Ltd.) Solvent: Methyl ethyl ketone

[0101] <Composition of Thermosetting Resin Composition> Boron nitride powder: 74.8 parts by weight Epoxy resin 1: 10.0 parts by weight Epoxy resin 2: 10.0 parts by weight Phenol-based hardener: 5.0 parts by weight ·Curing catalyst: 0.2 parts by mass

[0102] First, the epoxy resin, the phenol-based curing agent, and the curing catalyst were weighed according to the above <Composition of the thermosetting resin composition> and added to a solvent. This was stirred to obtain a mixed solution. Next, the boron nitride powder of each example was added to the mixed solution and premixed. After that, the mixture was stirred and mixed using a stirring blade to obtain a varnish-like thermosetting resin composition in which the boron nitride powder was uniformly dispersed.

[0103] <Preparation of Cured Product of Thermosetting Resin Composition (Cured Thermally Conductive Sheet)> Next, the obtained thermosetting resin composition of each example was aged under the condition of air atmosphere at 60°C for 15 hours. The obtained thermosetting resin composition was heat-treated at 100°C for 30 minutes to prepare a B-stage thermal conductive sheet having a thickness of 400 μm. Next, the above thermal conductive sheet was heat-treated at 180°C and 10 MPa for 40 minutes to obtain a thermal conductive sheet cured product having a thickness of 200 μm.

[0104] <Method of measuring thermal conductivity> The thermal diffusion coefficient (α), specific heat (Cp), and density (ρ) of the cured thermally conductive sheet of each example were measured by the methods described below. The thermal conductivity of the cured thermally conductive sheet was calculated from the thermal diffusion coefficient (α), specific heat (Cp), and density (ρ) according to the following formula (9). The unit of thermal conductivity is W / (m K). Equation (9): Thermal conductivity [W / (m·K)]=α[m 2 / s]×Cp[J / (kg K)]×ρ[kg / m 3 ]

[0105] <Measurement of thermal diffusion coefficient (α)> The thermal diffusion coefficient (α) of the cured thermal conductive sheet of each example was measured by the laser flash method (half-time method). The unit of the thermal diffusion coefficient (α) is m 2 / s. A test piece was obtained by cutting out a 10 mm x 10 mm piece from the cured thermally conductive sheet for thickness direction measurement. Next, the thermal diffusion coefficient (α) of the test piece in the thickness direction was measured by a non-steady method using a thermal conductivity measuring device (product name: LFA467, manufactured by NETZSCH). The measurement was performed under atmospheric conditions at 25°C.

[0106] <Measurement of specific heat (Cp)> The specific heat (Cp) of the cured thermally conductive sheet of each example was measured by DSC. The unit of specific heat (Cp) is J / (kg·K).

[0107] <Measurement of density (ρ)> The density (ρ) of the cured thermal conductive sheet of each example was measured in accordance with JIS K 6911:2006. Test pieces were cut out from the cured product of the thermosetting resin composition to a size of 20 mm length x 20 mm width. The unit of density (ρ) is kg / m 3 It is.

[0108] [Table 1] [Explanation of symbols]

[0109] 100 Metal base board 101 Metal Substrate 102 Insulating layer 103 Metal layer 200 Electronic equipment 201 Electronic Components 202 Adhesive layer 203 Bonding Wire 205 Sealing resin layer 207 Heat sink 209 Thermal Conduction Layer

Claims

1. The present invention includes a resin composition layer made of a thermosetting resin composition including a boron nitride powder containing boron nitride particles, the boron nitride powder having a plastic deformation initiation equivalent pressure of 5.0 MPa or more calculated by fitting to the Cooper-Eaton equation, and a thermosetting resin; A thermally conductive member, wherein the thermal conductivity of the cured product of the resin composition layer in the thickness direction is 10.0 W / (m·K) or more, as measured by a laser flash method.

2. A thermally conductive member as described in claim 1, wherein the boron nitride powder has an orientation degree A of 0.120 or more after compression by the following (Method 1). (Method 1) A cylindrical container having an inner diameter of 8.0 mm and a height of 40 mm is filled with 0.85±0.15 g of boron nitride powder. A load of 500 N is applied at a pressing speed of 0.2 mm / s twice in total to the container, thereby producing a compressed body of the boron nitride powder. In the X-ray diffraction spectrum of the compressed body obtained by the following <X-ray diffraction measurement method>, the diffraction peak intensity I of the 002 plane is 002 and the diffraction peak intensity I of the 100 plane 100 and, measuring The degree of orientation A after compression is calculated from the following formula (1). Equation (1): Degree of orientation after compression A = I 100 / I 002 <X-ray diffraction measurement method> X-ray diffraction is performed by irradiating the compressed body with X-rays in the thickness direction using CuKα radiation as a radiation source under conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scanning speed of 4° / min.

3. The volume-based median diameter D of the boron nitride powder measured by a laser diffraction scattering method 50 The thermal conductive member according to claim 1 or 2, wherein the average particle size is 0.1 μm or more and 100 μm or less.

4. The thermally conductive member according to claim 1 or 2, wherein the boron nitride powder contains scaly boron nitride particles.

5. 3. The thermally conductive member according to claim 1, wherein the boron nitride particles include secondary particles constituted by scaly primary particles of boron nitride.

6. A thermally conductive member as described in claim 1 or 2, wherein the filling rate of the boron nitride powder after compression at 10 MPa is less than 0.

74.

7. A thermally conductive member as described in claim 1 or 2, wherein the content of the boron nitride powder in the thermosetting resin composition is 50 mass% or more and 95 mass% or less when the total amount of the thermosetting resin composition (excluding the solvent) is 100 mass%.

8. The thermally conductive member according to claim 1 , wherein the thermosetting resin comprises an epoxy resin.

9. A thermally conductive member as described in claim 1 or 2, wherein the content of the thermosetting resin in the thermosetting resin composition is 5 mass% or more and 50 mass% or less when the total amount of the thermosetting resin composition (excluding the solvent) is 100 mass%.

10. A thermally conductive member as described in claim 1 or 2, wherein the thermosetting resin composition further contains a curing agent.

11. A thermally conductive member as described in Claim 10, wherein the content of the curing agent in the thermosetting resin composition is 0.01 mass% or more and 10 mass% or less when the total amount of the thermosetting resin composition (excluding the solvent) is 100 mass%.

12. The thermally conductive member according to claim 1 or 2, which is entirely in a sheet form.

13. The thermally conductive member according to claim 1 or 2, further comprising a substrate.

14. The thermally conductive member according to claim 1 or 2, wherein the resin composition layer is in an uncured state, a B-stage state, or a C-stage state.

15. A metal substrate, an insulating layer, and a metal layer, in this order; A metal-based substrate, wherein the insulating layer comprises the thermally conductive member of claim 14 .

16. A circuit board comprising the metal base substrate according to claim 15, The metal layer comprises a circuit layer.

17. A circuit board according to claim 16; and an electronic component on the circuit board.

18. A metal layer; an electronic component on a first surface of the metal layer; a thermally conductive member according to claim 14 on a second surface of the metal layer opposite the first surface; and a sealing resin layer that seals the electronic component and the metal layer.

19. A step of selecting boron nitride powder having a plastic deformation initiation equivalent pressure of 5.0 MPa or more calculated by fitting to the Cooper-Eaton equation; and applying a resin composition layer made of a thermosetting resin composition containing the selected boron nitride powder and a thermosetting resin onto a substrate, The method for producing a thermally conductive member, wherein the thermal conductivity in the thickness direction of the cured product of the resin composition layer is 10.0 W / (m·K) or more, as measured by a laser flash method.

20. 20. The method for producing a thermally conductive member according to claim 19, further comprising the step of selecting boron nitride powder having a degree of orientation A after compression of 0.120 or more by the following (Method 1). (Method 1) A cylindrical container having an inner diameter of 8.0 mm and a height of 40 mm is filled with 0.85±0.15 g of boron nitride powder. A load of 500 N is applied at a pressing speed of 0.2 mm / s twice in total to the container, thereby producing a compressed body of the boron nitride powder. In the X-ray diffraction spectrum of the compressed body obtained by the following <X-ray diffraction measurement method>, the diffraction peak intensity I of the 002 plane is 002 and the diffraction peak intensity I of the 100 plane 100 and, measuring The degree of orientation A after compression is calculated from the following formula (1). Equation (1): Degree of orientation after compression A = I 100 / I 002 <X-ray diffraction measurement method> X-ray diffraction is performed by irradiating the compressed body with X-rays in the thickness direction using CuKα radiation as a radiation source under conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scanning speed of 4° / min.

Citation Information

Patent Citations

  • Resin composition and method for producing the same

    JP2016108457A

  • Granulated powder, resin composition for heat dissipation, heat dissipation sheet, semiconductor device, and heat dissipation member

    JP2016127046A

  • Granulated powder, resin composition for heat dissipation, heat dissipation sheet, heat dissipation member, and semiconductor device

    JP2016192474A

  • Thermally conductive resin sheet, laminated heat dissipating sheet, heat-dissipating circuit board and power semiconductor device

    JP2022055740A

  • Method of manufacturing semiconductor device

    JP2023128645A

Cited By

  • Boron nitride powder, thermosetting resin composition, heat-conductive member, metal base substrate, circuit board, electronic device, and method for producing heat-conductive member

    WO2026004209A1